Carbon Dioxide Reduction Catalyzed by Dinuclear Ruthenium Polypyridyl Complexes. Issue 12 (26th August 2013) - Ono, Takashi; Planas, Nora; Miró, Pere; Ertem, Mehmed Z.; Escudero‐Adán, Eduardo C.; Benet‐Buchholz, Jordi; Gagliardi, Laura; Cramer, Christopher J.; Llobet, Antoni
Abstract Dinuclear ruthenium complexes [(Ru(bid))2(μ‐bpp)(μ‐OAc)] and [(Ru(trpy))2(μ‐bpp)(μ‐X)]2+ [X=Cl−, OAc−, and OCHO−; bpp=3, 5‐bis(2‐pyridyl)pyrazolato; bid−=(1Z, 3Z)‐1, 3‐bis(pyridin‐2‐ylmethylene)isoindolin‐2‐ide; trpy=2, 2':6', 2"‐terpyridine] were tested as catalysts for the hydrogenative reduction of carbon dioxide in the solvent 2, 2, 2‐trifluoroethanol in the presence of excess amine (triethylamine). Significant amounts of formic acid were produced by these catalysts, and a kinetic analysis based on initial rate constants was performed. These catalytic systems were investigated by using DFT calculations to elucidate the hydrogenative reduction mechanism. The results are compared with those obtained with previously reported mononuclear catalyst counterparts.